Psychosoma of Disabilities as Reflected in Professor Prem Singh’s Short Stories - Yadav, Mahabir Prasad (Literary Studies, 2015)
Disability is perennial international phenomenon which has been existing on the continuum of the world literature, education and society for over ages be it since the days of Homer and Tiresias in Greece, Milton, Pope and Byron in England, Louis Braille in France or Ashtavakra, Dirghatamas, Soordas, saint Virjanand and saint Gangeshwaranand in India. History and perspectives reveal that right since the days of antiquity to the postmodern and contemporary times of fourth world literature and society, disability community has been combating the odds for sustenance and self-esteem.